THE INFLUENCE OF ENGKLEK ON THE DEVELOPMENT OF MOTOR SKILLS IN PRESCHOOL CHILDREN AT TKIT RAFLESIA AND TKIT FITRI - Sartika, Nanda; Safitri, Meilani (Jurnal Mitra Kesehatan, 2025)
Introduction: Motor development in children is one of the fundamental  aspects that requires special attention because it supports children’s daily activities and their readiness to enter formal education. The prevalence of motor development difficulties in preschool children in Indonesia is fairly frightening, ranging from 52.5% to 54%.  The purpose of this study wa to examine the influence of engklek games on the gross and fine motor skills of preschool children at TKIT Raflesia and TKIT Fitri. Method: This study employed a descriptive quantitative approach with a pre-experimental design, especially a one-group pretest-posttest design with the sample size for this study was 77 preschool children from TKIT Raflesia and TKIT Fitri. The research instrument used was an observation sheet for hopscotch activities and children’s physical motor skills, employing the Wilcoxon Signed Ranks test for data analysis. Result: The research results provide evidence regarding the development of gross motor and the fine motor skills after engaging in the engklek game were statistically significant with a p-value of 0.000 (< 0.05). Conclusion: This study demonstrates that the engklek game significantly influences the development of both gross and fine motor skills in preschool children at TKIT Raflesia and TKIT Fitri (p = 0.000).